Recent Changes in the Treatment of Helicobacter pylori Infection in Children and Adolescents - Ji-Hyun Seo; Ji Sook Park; Hee-Shang Youn (Yong Chan Lee, 2021)
Treatments aimed at eradicating Helicobacter pylori (H. pylori) infections in children and adolescents should be clearly beneficial. According to the updated guidelines, a 14-day triple therapy or bismuth-based triple therapy is the first choice for treatment of children based on the results of antimicrobial sensitivity testing. Though culturing H. pylori using biopsy specimens is not always feasible, it should be performed for establishing empirical rescue therapy for patients not responding to first-line eradication therapy. The European and North American therapeutic strategies for children and adolescents with H. pylori infections may not be appropriate for treating children and adolescents in other countries owing to regional differences in epidemiological characteristics of H. pylori. The existence of clarithromycin-resistant H. pylori is an important factor involved in eradication failure. The development of new treatment-related allergies, treatment failure, side effects, and alteration of the gut microbiome have been highlighted as factors potentially outweighing the possible benefit of preventing future peptic ulcers or gastric cancer. Drug compliance can be improved by providing a detailed explanation of the reason for therapy, duration, and routes of drug administration. Physicians should understand the mechanisms underlying eradication treatment and explain drug prescriptions in detail to both parents and children to increase compliance. Herein, we reviewed the indications for and various modalities of eradication treatment in children with H. pylori infections in accordance with a review of recently published articles.